Strategic vigilance and its role in achieving the strategic direction: An exploratory study of the opinions of a sample of senior administrative leaders at the Holy University of Karbala - Awad Jarallah, Mohammed (Iraqi Journal for Administrative Sciences, 2024)
This research aims to measure the extent of the impact of strategic alertness in choosing the optimal strategic direction, and the conceptual and intellectual framework of this research is based on two basic variables, namely (strategic alertness and strategic direction). (Environmental vigilance, technological vigilance, competitive vigilance, marketing vigilance), while the dimensions of the strategic orientation were represented by (competitive orientation, analytical orientation, defensive orientation, future orientation, proactive approach), in addition to the statistical results reached by the field side of the research based on The questionnaire, whose paragraphs were designed with us in line with the nature of the research environment (University of Karbala), as the research came out with a set of conclusions, the most prominent of which is the existence of a strong and moral relationship and influence between strategic vigilance and strategic orientation, in the light of which a set of recommendations were raised for the university in question, which included a set of solutions The proposed tools for the development and advancement of the scientific level.